2020
DOI: 10.1111/lam.13252
|View full text |Cite
|
Sign up to set email alerts
|

Caution at choosing a particular colony-forming unit from faecal Escherichia coli: it may not represent the sample profile

Abstract: Significance and Impact of the Study: This study provides relevant data about the high phylogenetic and antimicrobial susceptibility diversity observed in Escherichia coli colony-forming units (CFUs) from a bacteriological culture of faeces from healthy calves, foals and lambs. The selection pressure exerted by the herd treatment may directly impact the intestinal microflora of animals that have never been treated. Finally, we emphasize the importance of Clinical Laboratory Standards Institute guidelines and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…mGEMS demonstrates the power of plate sweep sequencing in genomic epidemiology and enables a change in the currently dominant framework that confers multiple benefits over both whole-genome shotgun metagenomics and isolate sequencing. Studies of the population structures of opportunistic pathogens have revealed extensive strain-level within-host variation [21,23,27,67,68] with adverse implications for transmission analyses relying solely on isolate sequencing [31,69] and colony pick based longitudinal studies reporting the absence or re-emergence of strains in a host [30,38,70] or antimicrobial profiles [28,71]. While whole-genome shotgun metagenomics solves these issues to some extent [35,72], the culture-free nature suffers from issues with both bacterial and host DNA contamination particularly affecting the sensitivity for detecting strains in low abundance [29,33,34,73,74].…”
Section: Discussionmentioning
confidence: 99%
“…mGEMS demonstrates the power of plate sweep sequencing in genomic epidemiology and enables a change in the currently dominant framework that confers multiple benefits over both whole-genome shotgun metagenomics and isolate sequencing. Studies of the population structures of opportunistic pathogens have revealed extensive strain-level within-host variation [21,23,27,67,68] with adverse implications for transmission analyses relying solely on isolate sequencing [31,69] and colony pick based longitudinal studies reporting the absence or re-emergence of strains in a host [30,38,70] or antimicrobial profiles [28,71]. While whole-genome shotgun metagenomics solves these issues to some extent [35,72], the culture-free nature suffers from issues with both bacterial and host DNA contamination particularly affecting the sensitivity for detecting strains in low abundance [29,33,34,73,74].…”
Section: Discussionmentioning
confidence: 99%
“…mGEMS demonstrates the power of plate sweep sequencing in genomic epidemiology and enables a change in the currently dominant framework that confers multiple benefits over both whole-genome shotgun metagenomics and isolate sequencing. Studies of the population structures of opportunistic pathogens have revealed extensive strain-level within-host variation [20,22,26,54,55] with adverse implications for transmission analyses relying solely on isolate sequencing [30,56] and colony pick based longitudinal studies reporting the absence or re-emergence of strains in a host [29,37,57] or antimicrobial profiles [27,58]. While whole-genome shotgun metagenomics solves these issues to some extent [34,59], the culture-free nature suffers from issues with both bacterial and host DNA contamination particularly affecting the sensitivity for detecting strains in low abundance [28,32,33,60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, from the plates of each strain five colonies were selected (Maciel et al . 2019) and subjected to antimicrobial susceptibility test through the disk‐diffusion tests according to the Clinical Laboratory Standards Institute (CLSI 2012 – M02‐A11) guidelines with the following class drugs (Laborclin, Brazil): β‐Lactams—ampicillin (10 µg), amoxicillin–clavulanate (20/10 µg), cephalothin (30 µg); imipenem (10 µg); Macrolide – azithromycin (15 µg), erythromycin (15 µg); Aminoglycosides – amikacin (30 µg), gentamicin (10 µg), streptomycin (300 µg), tobramycin (10 µg); phenicols—chloramphenicol (30 µg); tetracyclines—doxycycline (30 µg); quinolones—enrofloxacin (10 µg), ciprofloxacin (5 µg); nitrofuran—nitrofurantoin (300 µg) and sulphonamides—trimethoprim/sulphamethoxazole (25 µg). Escherichia coli ATCC 25922 and ATCC 35218 were used as quality control strains.…”
Section: Methodsmentioning
confidence: 99%